C KONSEP PENDIDIKAN KARAKTER PERSPEKTIF AL-QUR'AN: Pendidikan Karakter, Ayat-Ayat Al-Quran tentang Pendidikan Karakter, Tujuan Pendidikan Karakter - Mei, Reski; Rofia Masrifah; Muhammad Yusuf; Ahmad Mujahid (Journal of Public Policy Analys, 2023)
This research aims to understand the issue of character education in Indonesia. Because up to this day, character issues in Indonesia continue to be a sharp focus of various groups. Various negative character traits have been prominently displayed by Indonesian society, often justified as if they were acceptable. There are numerous contemporary issues that we see, and it seems like they will never cease, such as the increasing prevalence of narcotics, even though many offenders are sentenced to death, bullying in schools, sexual crimes against students, online sexual transactions involving students, domestic violence, and more. This research discusses the Concept of Character Education According to the Quran, which explores several pieces of literature, books, and journals. In this research, data is gathered from books and journals related to the phenomenon of character education issues. References related to character education are based on the Quran, which encompasses the interpretation and instillation of values from an early age that align with family, school, and the environment. This study employs various methods, including case studies, literature analysis, and an analysis of the interpretation of Quranic verses related to the research topic. To gather data, the author collects, reads, and analyzes relevant discussions for the research. Character Education According to the Quran emphasizes the very important role that character education plays in shaping individuals with ethical values, morality, and good behavior. Thus, the significance of character education according to the Quran not only includes the formation of individual values but also contributes to the development of a better society in accordance with Islamic principles. In the Quran's perspective, character education is the path to moral perfection and social well-being.